Screening anticancer activity by Brine shrimp lethality test of extracts of Annona stenophylla (Engl. & Diels), Strophanthus petersianus (Klotzsch) and Synadenium glaucescens (Pax) - Roberto Luis Nhamussua; Faith Philemone Mabiki; Alinanuswe Joel Mwakalesi; Lyndy Joy McGaw (PLoS ONE, 2026)
Cancer continues to be one of the main public health challenges, driving the search for new compounds with therapeutic potential. Medicinal plants represent a valuable promising source of bioactive metabolites, and the Brine Shrimp Lethality Test has been widely used as a preliminary tool to assess the toxicity of natural extracts, providing clues to their possible anticancer activity. In this study, the cytotoxicity of the extracts of Annona stenophylla (Engl. & Diels), Strophanthus petersianus (Klotzsch), and Synadenium glaucescens (Pax) was investigated using the BSLT as a first step in screening for potential anticancer compounds. The plant materials were harvested in Tanzania and air-dried in the shade, and ground. The extracts were prepared by total sequential solvent extraction using cold maceration, starting with ethyl acetate, followed by methanol. A total of 24 ethyl acetate and methanolic extracts were obtained from the leaves, stem bark, stem wood, root wood and root bark of the three plants studied. The toxicity of the extracts was assessed by exposing Artemia salina nauplii to different concentrations of the extracts, with mortality recorded after 24 h. The LC 50 was determined to evaluate the toxicity of each extract. All the extracts from the three plants exhibited different degrees of toxicity, with A. stenophylla demonstrating the lowest LC 50 values, indicating the highest toxicity. The methanolic extract of A. stenophylla ’s root wood exhibited the highest toxicity, producing a mortality rate of 99.44%, corresponding to an LC 50 < 20 μg/mL. The observed toxicity suggests the presence of bioactive compounds with potential anticancer activities. The results support the potential of A. stenophylla , S. petersianus and S. glaucescens as sources of bioactive compounds with possible anticancer activity. Further studies, including phytochemical analysis and in vitro anticancer assays, are recommended to identify and characterize the active constituents responsible for the observed cytotoxic effects.